Mucocutaneous Adverse Reactions to COVID-19 Vaccines: Do Excipients Play a Role? - Leonardo Bianchi; Filippo Biondi; Katharina Hansel; Nicola Murgia; Alessandro D'Arpino; Marta Tramontana; Luca Stingeni (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)